INOVASI MODEL PEMBELAJARAN NHT (NUMBERED HEADS TOGETHER) BERBASIS MASALAH UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 1 PURWOREJO - Maylanova, Renata; Apri Setiaji, Cahyo; Rinawati, Anita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to: (1) develop a Problem-Based Numbered Heads Together (NHT) learning model that is effective in improving the critical thinking skills of Grade XI students at SMA Negeri 1 Purworejo; (2) determine the feasibility of the developed cooperative learning model based on content validity and appearance aspects assessed by experts; and (3) determine the practicality of the model based on teacher and student responses in economics learning. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The subjects were 72 students of classes XI I and XI J at SMA Negeri 1 Purworejo. Data were collected through expert validation sheets, response questionnaires, and pretest-posttest instruments. The data were analyzed using validity, practicality, t-test, and N-Gain analyses. The results showed that the developed learning model was categorized as very valid based on expert assessments. The practicality level of the model was also high according to student response questionnaires. The effectiveness of the model was demonstrated by a significant improvement in learning outcomes, with the mean pretest score increasing from 56.89 to 88.58 on the posttest. The t-test results indicated a significance value of less than 0.05, confirming a significant difference between pretest and posttest scores. Furthermore, the N-Gain score of 0.73 was classified as high, indicating that the NHT integrated with Problem-Based Learning (PBL) model is effective in enhancing students’ critical thinking skills.